Województwo lubuskie - potencjał infrastruktury regionu = Lubuskie province - the potential of the region`s infrastructure - Jakubowski, Edward (Zielona Góra: Lubuskie Towarzystwo Naukowe)
The new territorial division of the country was introduced by the administrative reform that came into effect on 1st January 1999. The essential purpose of the local government is to facilitate economic and technological development of the province, to improve the inhabitants` standards of living. The local government is supposed to compose the guidelines for the development of the province into its regional policy.
Keywords: województwo lubuskie; rozwój regionalny; gospodarka regionu